IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PADA SUB BAGIAN PELAYANAN KAPAL DI PT. PELABUHAN INDONESIA II (PERSERO) CABANG TELUK BAYUR - Mayang Arta Kencana; Yeni M Noer; Donna Ikranova Febrina (Jurnal Public Administration, Business and Rural Development Planning, 2023)
The results of the research in this study are : 1) the Implementation Of Management Information System In The Ship Service Sub Section at PT. Pelabuhan Indonesia II (Persero) Teluk Bayur Branch has used computerization in this case in the form of an application called SIMOPEL in its implementation includes several stages starting with the data collection stage, processing data using a SIMOPEL application, then producing output in the form of information or reports to management that are useful in decision making. Form the three stages it is known that the data input process often experiences problems, so that all service realization must be delayed for a while. 2) the factors that affect the Implementation Of Management Information System In The Ship Service Sub Section at PT. Pelabuhan Indonesia II (Persero) Teluk Bayur Branch are system errors and less extensive internet coverage, causing all implementation processes to be delayed and carried out manually. Based on the results of the research above, suggestions that the autor can propose are: 1) Continue to improve facilities and infastructure to support Implementation activities in the company. And improve each system at the stages of the existing procedures in the SIMOPEL application. 2) Improve the system on the application and the range of internet communication so that the Implementation Of Management Information System can operate properly.